PENGARUH TERPAAN IKLAN KOSMETIK MAYBELLINE DI TELEVISI DAN INTENSITAS KOMUNIKASI WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK MAYBELLINE - Nugrahini Tri Kusumaningrum, Dwi; Widowati Herieningsih, Sri (Interaksi Online, 2019)
Advertising is one of the sales promotion tools used by companies to market their products to the wider community. Advertisements are made as attractive as possible with the aim to attract the attention of the public to have the decision to buy a product. In addition, word of mouth / mouth to mouth communication is a strong factor to influence consumers in choosing products. The purpose of this study was to determine the effect of exposure to Maybelline cosmetic advertisements on television and the intensity of word of mouth communication on purchasing decisions of Maybelline cosmetic products. The theory used is Advertising Exposure Theory (Batra, Myers, and Aaaker, 2009) and Buyer Information Environment Theory (Liliweri, 1992). The sample technique used is non-probability sampling with a sampling method that is purposive sampling. The number of samples in this study were 100 respondents with special criteria, namely women aged 18-25 years, domiciled in the city of Semarang, had seen Maybelline advertisements on television, and had talked offline / face to face or online about Maybelline cosmetic products. The data analysis used is simple linear regression. The results of the study indicate that the significance value for the variable Maybelline cosmetic ad exposure on television is 0,000, which means very significant. This shows that there is an influence between exposure to Maybelline cosmetic advertisements on television (X1) to the purchase decision of Maybelline (Y) cosmetic products to be exact at 51.8 percent. Furthermore, the variable intensity of word of mouth communication found a significance value of 0,000, which means very significant. Then there is the effect of the intensity of word of mouth communication (X2) on the purchase decision of Maybelline (Y) cosmetic products precisely at 53.2 percent. The conclusion of this study is the variable exposure to Maybelline cosmetic advertisements on television and the intensity of word of mouth communication affect the purchasing decisions of Maybelline cosmetic products. But with these results, it is suggested to Maybelline Indonesia to be able to create a tagline that is easier for consumers to remember, and to hold creative campaigns on interactive social media by including hastag (#) or making interesting quizzes to further improve consumer purchasing decisions.